A Randomized Phase IIb Study of Mavrilimumab and Golimumab in Rheumatoid Arthritis - Weinblatt, Michael E; McInnes, Iain B; Kremer, Joel M; Miranda, Pedro; Vencovsky, Jiri; Guo, Xiang; White, Wendy I; Ryan, Patricia C; Godwood, Alex; Albulescu, Marius; Close, David; Burmester, Gerd R (Arthritis & rheumatology (Hoboken, N.J.), 2018)
OBJECTIVE: This 24-week, phase IIb, double-blind study was undertaken to evaluate the efficacy and safety of mavrilimumab (a monoclonal antibody to granulocyte-macrophage colony-stimulating factor receptor α) and golimumab (a monoclonal antibody to tumor necrosis factor [anti-TNF]) in patients with rheumatoid arthritis (RA) who have had an inadequate response to disease-modifying antirheumatic drugs (DMARDs) (referred to as DMARD-IR) and/or inadequate response to other anti-TNF agents (referred to as anti-TNF-IR). METHODS: Patients with active RA and a history of DMARD-IR (≥1 failed regimen) or DMARD-IR (≥1 failed regimen) and anti-TNF-IR (1-2 failed regimens) were randomized 1:1 to receive either mavrilimumab 100 mg subcutaneously every other week or golimumab 50 mg subcutaneously every 4 weeks alternating with placebo every 4 weeks, administered concomitantly with methotrexate. The primary end points were the American College of Rheumatology 20% improvement (ACR20), 50% improvement, and 70% improvement response rates at week 24, percentage of patients achieving a Disease Activity Score in 28 joints using C-reactive protein level (DAS28-CRP) of <2.6 at week 24, percentage of patients with a score improvement of >0.22 on the Health Assessment Questionnaire (HAQ) disability index (DI) at week 24, and safety/tolerability measures. This study was not powered to formally compare the 2 treatments. RESULTS: At week 24, differences in the ACR20, ACR50, and ACR70 response rates between the mavrilimumab treatment group (n = 70) and golimumab treatment group (n = 68) were as follows: in all patients, -3.5% (90% confidence interval [90% CI] -16.8, 9.8), -8.6% (90% CI -22.0, 4.8), and -9.8% (90% CI -21.1, 1.4), respectively; in the anti-TNF-IR group, 11.1% (90% CI -7.8, 29.9), -8.7% (90% CI -28.1, 10.7), and -0.7% (90% CI -18.0, 16.7), respectively. Differences in the percentage of patients achieving a DAS28-CRP of <2.6 at week 24 between the mavrilimumab and golimumab groups were -11.6% (90% CI -23.2, 0.0) in all patients, and -4.0% (90% CI -20.9, 12.9) in the anti-TNF-IR group. The percentage of patients achieving a >0.22 improvement in the HAQ DI score at week 24 was similar between the treatment groups. Treatment-emergent adverse events were reported in 51.4% of mavrilimumab-treated patients and 42.6% of golimumab-treated patients. No deaths were reported, and no specific safety signals were identified. CONCLUSION: The findings of this study demonstrate the clinical efficacy of both treatments, mavrilimumab at a dosage of 100 mg every other week and golimumab at a dosage of 50 mg every 4 weeks, in patients with RA. Both regimens were well-tolerated in patients who had shown an inadequate response to DMARDs and/or other anti-TNF agents.
Keywords: dospělí; Arthritis, Rheumatoid; Female; revmatoidní artritida; Adult; výsledek terapie; mladý dospělý; ženské pohlaví; Tumor Necrosis Factor-alpha; Adolescent; Antibodies, Monoclonal; lidé; dvojitá slepá metoda; Treatment Outcome; Aged, 80 and over; stupeň závažnosti nemoci; Methotrexate; TNF-alfa; Double-Blind Method; Male; Aged; methotrexát; Antirheumatic Agents; Young Adult; monoklonální protilátky; humanizované monoklonální protilátky; senioři nad 80 let; lidé středního věku; senioři; mužské pohlaví; Antibodies, Monoclonal, Humanized; Severity of Illness Index; antirevmatika; Middle Aged; mladiství; Humans